VR-TECHNOLOGY AS A METHOD AND MEANS OF TRAINING - Trach, Yuliya (Educological discourse, 2017)
The paper drawn attention to one of the most promising educational methods offered by modern information technologies - virtual reality, computer modeled and considered as a special information environment in which all objects are in three dimensions. The real research of virtual reality in teaching done very little. Authors of papers available technology reduces the use of virtual education to the use of electronic textbooks and test membranes, multimedia less, in some cases - computer simulation and virtual simulators. Therefore, the purpose of this article - summarizing experience exploring the possibilities of using VR technology in the educational process. Advantages (visibility, security, engagement, focus, virtual classes) and disadvantages (depth disciplines, the cost of devices for BP, clarity and understandability of context, the need to upgrade existing educational programs) use of VR technologies in education; VR formats in education (full-time, distance learning, blended education, self-education). An application of the best projects in the educational process BP (LABSTER, EXPEDITIONS PIONEER PROGRAM, VIRTUAL REALITY MEDICAL TRAINING SIMULATION, LECTURE VR). It was concluded that BP technology today - a further possibility of using something new, develop cognitive skills, increasing interest in the subject. However, there are certain conditions, compliance with which will promote the effective implementation of virtual education opportunities. This motivational readiness of students to pursue opportunities for virtual education as a means of intensifying; sophistication of information technology skills to implement virtual education opportunities; creative activity and independence of students in the implementation of virtual education opportunities.